Sustainable radical approaches for cross electrophile coupling to synthesize trifluoromethyl- and allyl-substituted tert-alcohols - Muhammad Awais Ashraf (Elsevier, 2021)
Summary: Trifluoromethylated molecules have gained privileged recognition among the medicinal and pharmaceutical chemists. Sustainable photoredox- and electrochemical processes were employed to facilitate the relatively less explored radical cross-electrophile coupling to access trifluoromethyl- and allyl-substituted tert-alcohols. Reactions proceed through trifluoromethyl ketyl radical and allyl radical intermediates, which undergo challenging radical-radical cross-coupling. The developed transformations are mild and chemo-selective to give cross-coupled products and deliver a wide range of valuable trifluoromethyl- and allyl-containing tertiary alcohols. Both processes can also be applied for the synthesis of amine variant containing trifluoromethyl and allyl moiety, which is considered as amide bioisostere.